The Features of Children with Tuberculosis at Sidawangi Pulmonary Hospital in Indonesia: Interactions within the Home as a Potential Transmission Risk - Pratiwi, Witri; Toipah, Iip; Rachmawan, Yogi Puji; Reki, Winarto (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Tuberculosis (TB) is an infectious disease that can infect children. The prevalence of pediatric TB in Indonesia has increased in recent years, causing a major burden on children's health. Aims: To determine the characteristics of pediatric TB patients at Sidawangi Pulmonary Hospital, West Java Province, Indonesia. Methods: A cross-sectional study was conducted at Sidawangi Pulmonary Hospital, West Java Province, Indonesia. The samples were new cases of pediatric TB from January 2020 to July 2023. Data were collected and analyzed from outpatient and inpatient medical records. Logistic regression was used to analyze the association between age and household contact. Results: There were 190 pediatric TB patients collected during the study period. Most of them were less than 5 years old (37.9%). The proportion of male and female was almost same. Most pediatric TB patients had household contacts (73.7%), especially those <1 year old. TB patients aged <1 year had an AOR of 31.94 (95%CI 3.8–268.35) for household contact compared to those aged 10-17 years. Conclusion: Pediatric TB patients at Sidawangi Pulmonary Hospital are mostly less than 5 years old. Compared to older age groups, pediatric TB patients aged <1 year had the highest proportion of household contacts. The government needs to pay attention to the risk of TB transmission to children through household contact, especially in younger children. Received: 27 January 2025 | Reviewed: 11 February 2025 | Revised: 22 February 2025 | Accepted: 23 February 2025.